A lithostratigraphic reappraisal of a Permian-Triassic fluvial succession at Allan Hills (Antarctica) and implications for the terrestrial end-Permian extinction event - Cornamusini, G.; Zurli, L.; Liberato, G. P.; Corti, V.; Gulbranson, E. L.; Perotti, M.; Sandroni, S. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)
Between Permian to Triassic, the Earth experienced climatic and biotic crises, included the greatest mass extinction at the Permian-Triassic boundary. These climatic and biological changes are reflected in both marine and terrestrial depositional systems. Over this time span, the Gondwana supercontinent hosted numerous large basins that may preserve the paleoenvironment response to global changes in the sedimentary record. This study provides a lithostratigraphic reappraisal of the latest Paleozoic-Mesozoic alluvial Beacon Supergroup at Allan Hills (Convoy Range), which is one of the most complete sedimentary sequences in Antarctica. Fieldwork stratigraphic-lithological observation, facies analysis, and petrographic characterization of sedimentary rocks allow the identification of six depositional units. The investigations point out for a conformable relationship between depositional and lithostratigraphic units, characterized by changes in the fluvial style. The reconnaissance of a “transitional interval” showing intermediate features between the Permian Weller Coal Measures and the Triassic Feather Conglomerate strengthen the conformable nature of the sequence across the Permian-Triassic boundary in this region. The lithological features of such interval strongly resemble those observed in the coeval deeply studied Eastern Australia successions crossing the Permian-Triassic boundary as well as the end-Permian extinction. More precisely, the uppermost coal occurrence, just above a glossopterid macroflora-bearing carbonaceous mudstone within the “transitional interval”, marks the disappearance of coal-peat forming Permian vegetation which corresponds with the terrestrial end-Permian extinction, thus representing one of the few end- Permian extinction records in Antarctica.